2014
DOI: 10.1039/c3ra46790b
|View full text |Cite
|
Sign up to set email alerts
|

Direct laser micropatterning of GeSe2 nanostructures film with controlled optoelectrical properties

Abstract: We demonstrate that a direct focused laser beam irradiation is able to achieve localized modification on GeSe 2 nanostructures (NSs) film. Using scanning focused laser beam setup, micropatterns on GeSe 2 NSs film are created directly on the substrate. Controlled structural and chemical changes of the NSs are achieved by varying laser power and treatment environment. The laser modified GeSe 2 NSs exhibit distinct optical, electrical and optoelectrical properties. Detailed characterization is carried out and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…1d . In similar way, it is reported that the position of main O 1s peak which remains bonded with GeO x at BE of 531.2 ± 0.2 eV while the rest one at 532.1 ± 0.2 eV indicates the chemisorbed oxygen 32 . In our study, V O ’s plays the most important role to originate the formation-free resistive switching via oxidation state changes of Ge 4+ /Ge 0 in W/GeO x /W structure.…”
Section: Resultssupporting
confidence: 75%
“…1d . In similar way, it is reported that the position of main O 1s peak which remains bonded with GeO x at BE of 531.2 ± 0.2 eV while the rest one at 532.1 ± 0.2 eV indicates the chemisorbed oxygen 32 . In our study, V O ’s plays the most important role to originate the formation-free resistive switching via oxidation state changes of Ge 4+ /Ge 0 in W/GeO x /W structure.…”
Section: Resultssupporting
confidence: 75%
“…These demonstrations indicate that the focused laser pruning could enhance the potential of these CdS x Se 1ex nanobelts in optoelectronic applications as photoswitches and photodetectors. Similar conductivity and photoconductivity modification was observed in laser pruning of GeSe 2 nanoribbons [19] . Around 3 times increase in the output current after laser modification at 10 V is revealed by the dark IeV curves.…”
Section: Property Modification Via Focused Laser Beammentioning
confidence: 52%
“…Our group demonstrated laser pruning induced electrical and photoelectrical property enhancement by characterization of CdS x Se 1ex and GeSe 2 nanobelts [19,20] . The pristine CdS x Se 1ex nanobelts are poor conductors as shown by the typical IeV curve in Fig.…”
Section: Property Modification Via Focused Laser Beammentioning
confidence: 98%
See 1 more Smart Citation
“…Annealing is observed to induce slight peak shifts, but more notably an increase in the GeO x intensity, which is indicative of surface oxidation. 40 Figure 3g highlights the changes in the Se-3d peak from annealing. There is a blueshift in the peak, which is suggestive of spin−orbit splitting.…”
Section: Nano Lettersmentioning
confidence: 99%